2006
DOI: 10.2105/ajph.2004.057281
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Screening Adolescents for Suicide Risk in “Real-World” High School Settings

Abstract: A simpler, more specific screening instrument than the Suicide Risk Screen would identify approximately 11% of urban high school youths for assessment, offering high school officials an important opportunity to identify young people at the greatest levels of need and to target scarce health resources. Our experiences from this study show that lack of feasibility testing greatly contributes to the gap between science and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 33 publications
5
92
1
4
Order By: Relevance
“…Moreover, results showed that a higher level of hopelessness was associated with a higher level of adolescent suicidal ideation. This observation is consistent with previous literature (e.g., Hallfors et al, 2006;Rucklidge, 2006;Smith et al, 2006). Adolescents feeling hopeless might regard suicidal ideation or suicidal behavior as the only alternative available and wrongfully put their hopes on life after death (Tse & Bagley, 2002;Yip, et al, 2006).…”
Section: Discussion 15supporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, results showed that a higher level of hopelessness was associated with a higher level of adolescent suicidal ideation. This observation is consistent with previous literature (e.g., Hallfors et al, 2006;Rucklidge, 2006;Smith et al, 2006). Adolescents feeling hopeless might regard suicidal ideation or suicidal behavior as the only alternative available and wrongfully put their hopes on life after death (Tse & Bagley, 2002;Yip, et al, 2006).…”
Section: Discussion 15supporting
confidence: 92%
“…For instance, a significant relationship between hopelessness and suicidality has been obtained (e.g., Cukrowicz et al, 2004;Rutter et al, 2004), with hopelessness as the best predictor of suicidal ideation among student and adolescent samples suffering from bipolar disorder (Hallfors et al, 2006;Rucklidge, 2006). Another individual factor, a person's emotional competence, has been related to depression and mental health (Miner et al, 2001;Znoj et al, 2002), and a lack of 5 social problem-solving ability seems to be closely linked with suicidal behavior (e.g., Carrie et al, 1998;Yang & Clum, 1996).…”
mentioning
confidence: 99%
“…Among "typical" students selected to participate, about 65% "typical" completed the survey. There were no significant differences between the "typical" students who took part in the study and the overall pool of "typical" students (Hallfors et al, 2006a …”
Section: Subjectsmentioning
confidence: 86%
“…Personal attitudes toward suicide may play an important role in predicting suicidal behaviors (see, e.g., Hallfors et al, 2006a). However, relatively little attention has been paid to this measure.…”
Section: Discussionmentioning
confidence: 99%
“…Ésta se realizará en adolescentes no consultantes, escolarizados, por varias razones. En primer lugar, porque la gran mayoría de los sujetos de ese grupo de edad están cursando estudios de enseñanza media 5 ; y, los colegios ofrecen la posibilidad de actuar sobre ellos en forma sistemática, de modo que conociendo su realidad, a futuro se pueden planificar estrategias preventivas 19,20 . En segundo lugar, porque es conocido el hecho de que los jóvenes en riesgo, aún después de un intento, rara vez consultan a un médico 19,21,22 .…”
Section: Artículo De Investigaciónunclassified